Unlocking the Potential: A Review of Stem Cell Applications in Regenerative Medicine - Zulda Musyarifah; Rizki Rahmadian (Frontiers on Healthcare Research)
Background : Regenerative medicine stands at the forefront of transformative healthcare, offering innovative approaches to address tissue damage and degenerative conditions. Central to this paradigm is the profound impact of stem cell therapy, a dynamic and promising avenue within regenerative medicine. As we navigate the complexities of this evolving field, our systematic literature review seeks to unravel the diverse applications, breakthroughs, and challenges inherent in utilizing stem cells for regenerative purposes